2016
DOI: 10.1158/0008-5472.can-15-2510
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tumor Kinase (Brk/PTK6) Is Induced by HIF, Glucocorticoid Receptor, and PELP1-Mediated Stress Signaling in Triple-Negative Breast Cancer

Abstract: Cancer cells use stress response pathways to sustain their pathogenic behavior. In breast cancer, stress response-associated phenotypes are mediated by the breast tumor kinase, Brk (PTK6), via the hypoxia-inducible factors HIF-1α and HIF-2α. Given that glucocorticoid receptor (GR) is highly expressed in triple negative breast cancer (TNBC), we investigated crosstalk between stress hormone-driven GR signaling and HIF-regulated physiologic stress. Primary TNBC tumor explants or cell lines treated with the GR lig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 51 publications
5
46
0
Order By: Relevance
“…The study of GR's role in basal-like breast cancer has important clinical implications because potent synthetic glucocorticoids are often prescribed to breast cancer patients undergoing chemotherapy to prevent side-effects such as nausea, loss of appetite, and rare severe immune reactions. Our preliminary data supports a handful of other studies that report that induction of GR with glucocorticoids could promote tumor growth and therapy resistance (15,17,18,52). In our study specifically, it is clear that glucocorticoid induction of GR leads to increased cell proliferation in basal-like breast cancer cell lines and patient-derived organoids.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study of GR's role in basal-like breast cancer has important clinical implications because potent synthetic glucocorticoids are often prescribed to breast cancer patients undergoing chemotherapy to prevent side-effects such as nausea, loss of appetite, and rare severe immune reactions. Our preliminary data supports a handful of other studies that report that induction of GR with glucocorticoids could promote tumor growth and therapy resistance (15,17,18,52). In our study specifically, it is clear that glucocorticoid induction of GR leads to increased cell proliferation in basal-like breast cancer cell lines and patient-derived organoids.…”
Section: Discussionsupporting
confidence: 90%
“…The role of many TFs have been studied in basal-like breast cancer, including oncogenic drivers such as MYC (6), and other TFs that regulate pathways associated with basal-like phenotypes such as EN1 (7), GLI1 (8), NF-kB (9), HIF1a (10), TWIST1 (11), FOXC1 (12,13), AP-1 (14), GR (15)(16)(17)(18), STAT3 (19,20), and MAFK (21). Many of these TFs regulate important pathways in basal-like breast cancer and these TFs often regulate each other's expression (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al found there to be extensive cross-talk between the GR and the hypoxia-inducible factors (HIF) where the HIF created upregulation of Brk, a breast tumor kinase. The authors suggest that identifying ways to target and reduce Brk expression could be helpful in treating patients whose tumors are both PR and ER negative 43) .…”
Section: Cortisol and Breast Cancer: Molecular Evidencementioning
confidence: 99%
“…However, the divergent roles of these receptors in driving breast cancer growth complicates their use, and necessitates further study for patient selection [13, 14]. There is also recent interest in the role of GR in breast cancer, particularly the ER− subtypes [2428]. PDX models that express each of these receptors in different combinations will be critical to evaluate new steroid receptor-targeted drugs and make selections for appropriate candidates for treatments.…”
Section: Steroid Hormone Receptors In Breast Cancermentioning
confidence: 99%